CASE STUDY - A WAY OF TEACHER'S CREATIVITY DEVELOPMENT - Petr, MACH (Trends in education, 2009)
One of the ways to improve didactic preparation of students is to use case study method. Case study is a complex and creative solution of a given didactic situation in a simulated didactic environment. Didactic situation is understood as short-term interaction between teacher and pupils that is defined by the content and the way of solution, i.e. the chosen methods, means and forms. This application brings good results when forming basic teacher competences. It helps to minimize fear of failure at first performances during teaching practice. It is a very progressive field of applied pedagogic research.
Keywords: case study; teacher competences; teaching practice; pedagogic research.